Profitability, Corporate Governance, Corporate Social Responsibility, And Firm Value - Dita Dwi Purnama Sari; Tatang Ari Gumanti (International Journal of Economics Accounting and Management, 2025)
This study investigates the influence of profitability, corporate governance, and corporate social responsibility on firm value among food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023.  The sample consists of 33 firms that meet the selection criteria, resulting in 132 firm-year data points.  The analysis utilizes panel data regression using a multiple linear regression model to evaluate the relationships among the variables. The empirical findings indicate that profitability and robust corporate governance positively and significantly impact business value, implying that increased returns and effective governance structures improve market perception and investor confidence. In contrast, corporate social responsibility has a negative correlation, suggesting that CSR initiatives may not immediately enhance business value within the analyzed timeframe, maybe due to immediate cost repercussions. These findings underscore the essential importance of profitability and governance in maintaining company value, while also indicating the necessity for a strategic approach to CSR implementation within the food and beverage sector.